Analysis of Main Protection Replacement of Bay Line Parepare - Suppa from Distance Relay to Line Current Differential Relay of 150 kv Parepare Substation - Fattah, Darmin; Sultan, Ahmad Rizal; Gaffar, Ahmad (Jurnal Teknologi Elekterika, 2025)
Bay Line Parepare - Suppa uses relay distance as the main safety. With a short transmission line distance, a reliable protection system is needed to overcome disturbances that occur in the system. With the development of time, and also to further improve the main transmission safety, the distance relay as the main protection is replaced with LCD (Line Current Differential) with changes in SPLN T5.002: 2010 to SPLN T5.002: 2021. This study aims to characterize the impedance value, the results of the SIR (Source Impedance Ratio) process and the effect of revenue obtained in replacing the main protection of the Parepare - Suppa bay line from relay distance to LCD (Line Current Differential) relay. Based on the calculation of the impedance seen in the relay distance on the Parepare - Suppa high voltage overhead line, the results are very small (0.1286 - 0.321 ohms). The results of the analysis show that the Source Impedance Ratio (SIR) obtained on the Parepare - Suppa conductor is 4.015 Ohm, while after replacing the relay, the gain or profit obtained is Rp. 1,112,340,880, -